Analisis Kebijakan Pengawakan Kapal Niaga - Darusalam, Adaud; Lubis, Lunariana; Marsudi, Sugeng (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2023)
To fulfil one aspect of shipping safety as a support for smooth ship traffic at sea, it is necessary to have a crew that has expertise, abilities and skills. Thus, every ship that will sail must be manned with sufficient and capable crew to perform their duties on board in accordance with their respective positions by considering the tonnage of the ship, the arrangement of the ship's machinery and the shipping area. This is in accordance with the contents of the Minister of Transportation Regulation No. PM 26 of 2022 concerning the manning of commercial vessels. The purpose of this research is to analyse the commercial ship manning policy at PT SPIL Surabaya and its supporting and inhibiting factors. This research uses qualitative research with a case study approach and George Edwards III implementation theory. The results obtained that the Minister of Transportation Regulation Policy Number PM 26 of 2022 concerning Commercial Ship Manning at PT SPIL Surabaya has been implemented quite well.